1994
DOI: 10.1111/j.1365-2958.1994.tb00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Replication control of plasmid R1: disruption of an inhibitory RNA structure that sequesters the repA ribosome‐binding site permits tap‐independent RepA synthesis

Abstract: The replication frequency of plasmid R1 is controlled by an antisense RNA, CopA, that inhibits the synthesis of the replication initiator protein, RepA, at the post-transcriptional level. This inhibition is indirect and affects translation of a leader peptide reading frame (tap). Translation of tap is required for repA translation (Blomberg et al., 1992). Here we asked whether an RNA stem-loop sequestering the repA ribosome-binding site blocks tap translation-independent repA expression. Destabilization of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…This plasmid was called pGW258 (Table 3). The fusion plasmids of the pGW77-L series were obtained by transferring the repA-lacZ segments from plasmids of the pGW177-L series (Blomberg et al, 1994), bordered by Bgl II and XbaI sites, into pGW258, cleaved with the same enzymes. Plasmid pGB2 P BAD lac was constructed by cutting pGB2 with XmaI and Hin dIII and ligating in an SgrA1-Hin dIII fragment cut from pBADLAC (McLennan et al, 1994) and containing araC P BAD lac.…”
Section: Bacterial Strains and Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…This plasmid was called pGW258 (Table 3). The fusion plasmids of the pGW77-L series were obtained by transferring the repA-lacZ segments from plasmids of the pGW177-L series (Blomberg et al, 1994), bordered by Bgl II and XbaI sites, into pGW258, cleaved with the same enzymes. Plasmid pGB2 P BAD lac was constructed by cutting pGB2 with XmaI and Hin dIII and ligating in an SgrA1-Hin dIII fragment cut from pBADLAC (McLennan et al, 1994) and containing araC P BAD lac.…”
Section: Bacterial Strains and Plasmidsmentioning
confidence: 99%
“…They act by binding to and inhibiting the function of a target RNA. Two Escherichia coli systems that have been well characterized are the IncFII plasmids, in which the antisense RNA, CopA, interacts with its mRNA target to inhibit translation of an essential replication initiator protein (Nordström et al, 1984;Blomberg et al, 1994;Malmgren et al, 1996), and the ColE1-related plasmids, in which the antisense RNA, RNA I, prevents the maturation of a preprimer RNA (Tomizawa et al, 1981). There is considerable similarity in the way in which these systems work.…”
Section: Introductionmentioning
confidence: 99%
“…CopA binds to the leader region of the repA mRNA (CopT), located about 80 nt upstream of the repA start codon (Fig+ 1)+ Binding prevents tap translation and thereby repA expression (Blomberg et al+, , 1994Malmgren et al+, 1996)+ The CopA-CopT binding process is viewed as a series of reactions leading to progressively more stable complexes (Persson et al+, 1988(Persson et al+, , 1990a(Persson et al+, , 1990bMalmgren et al+, 1997)+ CopA and CopT are fully complementary and both RNAs contain a major stem-loop structure (II/II9 in Fig+ 1) that is essential for high pairing rates and control (Öhman & Wagner, 1989;Hjalt & Wagner, 1992, 1995+ The initial step involves a transient looploop interaction (kissing complex) between the complementary hairpin loops (Persson et al+, 1990a(Persson et al+, , 1990b)+ Indeed, a truncated CopA (CopI, Fig+ 1), lacking the 59 proximal 30 nt and consisting only of the major stemloop, does not form stable duplexes with CopT, but is capable of competing with CopA for binding (Persson et al+, 1990b)+ It was recently shown that in both CopICopT and CopA-CopT complexes, initial kissing is rapidly followed by more extended intermolecular interactions (Malmgren et al+, 1997)+ Subsequently, the single-stranded region in the 59 tail of CopA pairs with its complement in CopT to yield the stable, inhibitory CopA-CopT complex+ This complex is the dominant product of binding in vitro (Malmgren et al+, 1996(Malmgren et al+, , 1997+ Complete duplex formation is very slow and has been proposed to be irrelevant for control (Malmgren et al+, 1996(Malmgren et al+, , 1997Wagner & Brantl, 1998)+ Different pairing pathways that result in rapid formation of stable antisense-target RNA complexes have been described (Kittle et al+, 1989;Persson et al+, 1990b;Tomizawa, 1990;Siemering et al+, 1994;Thisted et al+, 1994)+ A common feature is the use of a restricted single-stranded region in each interacting RNA for the initial step+ In most cases, binding initiates between two loops, in some cases between a loop and a singlestranded RNA segment+ Subsequently, more stable complexes are either formed by the pairing of distal RNA segments or, in the latter case, by extension of the first helix+…”
Section: Introductionmentioning
confidence: 99%
“…Sequences and secondary structures of the antisense RNA (CopA) and of the leader segment of the repA mRNA+ Structures are based on chemical and enzymatic probing (Öhman & Wagner, 1989; this work)+ The target sequence (CopT) of the antisense RNA (CopA) is shown in brackets+ The Shine and Dalgarno (SD), stop codon of tap, and start codons of tap and repA are indicated+ Binding of CopA prevents translation of the tap reading frame by occluding ribosome binding at tap initiation site (Ϫ)+ Under these conditions, the stable RNA stem-loop that sequesters the repA ribosome binding site (RBS) prevents translation of the repA reading frame (Blomberg et al+, 1994)+ If CopA fails to bind, ribosomes translate the tap reading frame, terminate at the tap stop codon, and reinitiate at the repA RBS by a direct translational coupling (Blomberg et al+, , 1994)+ The sequence of the truncated antisense RNA (CopI) sufficient to inhibit tap translation is boxed Malmgren et al+, 1996)+ are clearly similar+ In all these systems, it was suggested that an initial loop-loop interaction is rapidly converted to an extended kissing complex+ This requires partial melting of the upper stem regions, most probably facilitated by the presence of bulged residues (Siemering et al+, 1994;Hjalt & Wagner, 1995)+ Interestingly, the extended kissing complex suffices for inhibition in vivo Wilson et al+, 1993)+ In the case of plasmid R1, the extended kissing complex is also capable of blocking ribosome binding at the tap translation initiation site in vitro (Malmgren et al+, 1996), suggesting the existence of a bulky structure+…”
Section: Introductionmentioning
confidence: 99%
“…Antisense RNAs encoded by IncFII plasmids also follow a similar binding pathway (27). Nevertheless, the translation of rep genes encoded by these plasmids does not require formation of a pseudoknot (9,28), unlike the case for IncI␣ (13) and IncB (15) plasmids. Instead, IncFII plasmids additionally encode a transcriptional repressor for the rep mRNA, located upstream of the repressible promoter (3) (see Fig.…”
Section: Molecular Basis For Differential Control Of Repy and Repz Bymentioning
confidence: 99%